CHOROIDAL BLOOD FLOW VISUALIZATION IN HIGH MYOPIA USING A PROJECTION ARTIFACT METHOD IN OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 3 (March 2017) - Maruko, Ichiro; Spaide, Richard F.; Koizumi, Hideki; Sawaguchi, Shota; Izumi, Takahiko; Hasegawa, Taiji; Arakawa, Hisaya; Iida, Tomohiro
Abstract : Purpose: To visualize choroidal blood flow in larger vessels in highly myopic eyes using a phenomenon of the projection artifact to in the sclera using optical coherence tomography angiography. Methods: The retrospective study included 92 eyes (54 patients) with greater than 8 diopters of myopia. All eyes were examined using optical coherence tomography angiography (RTVue XR Avanti; Optovue Inc, Fremont, CA). The blood flow in choroidal vessels was evaluated by attempting to directly segment the choroid and also by placing the segmentation layer behind the choroid, within the sclera. Subfoveal choroidal thickness was also measured at the same time. The authors also evaluated the 54 normal eyes (54 cases) without high myopia as a control group. Results: Segmentation artifacts occurred in 68 cases (73.9%) and precluded direct visualization of the choroidal blood flow in larger vessels. When the segmentation slab was placed posterior to the choroid within the sclera, the choroidal blood flow was visualized in 41 eyes (44.6%). The mean subfoveal choroidal thickness in eyes with visualization of choroidal blood flow was thinner than without visualization (50.3 ± 42.2 μ m vs. 100.3 ± 44.4 μ m, P < 0.01). Choroidal blood flow in larger vessels was imaged in no control eye. Conclusion: The choroidal vessel anatomy could be imaged by detecting flow using the projection artifact in the sclera with optical coherence tomography angiography. This technique may be useful in estimating the vascularity of the choroid. Abstract : Supplemental Digital Content is Available in the Text.Although en-face optical coherence tomography angiography cannot visualize the choroidal blood flow in larger vessels in emmetropic eyes, choroidal blood flow in highly myopic eyes was visualized in 44.6% of cases by using a novel technique of imaging the projection artifact from the sclera.